การประยุกต์ใช้เทคนิคจำลองสถานการณ์เพื่อสร้าง สมดุลโซ่อุปทาน: กรณีศึกษา บริษัทโตเกียวคอยล์ เอ็นจิเนียร์ (ประเทศไทย) จำกัด - โยคินทร์ อินเหยี่ยว (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The objective of this research is to improve the work flow processes involved with regards to the electronically manufactured production of transformer coils, by focusing on improving productivity and line balancing of the supply chain for circumspect consideration and determination, both Logistics and Supply Chain Management Theory and Introduction to Lean Manufacturing were applied as factors for establishing reductions in non-value processes-Wastes/MUDA. This included finding a solution to improve the work cell by applying the ECRS (E-Eliminate, C-Combine, R-Re-arrange and S-Simplify) principles. To improve the transformer oil production processes, the Arena Program, which is simulation software, was used to develop new improvements to the design. This research provided 2 simulation models which were: Model 1 : A simulation of the current transformer coil production process- 11 work cells. Model 2 : A simulation for the improvement of work flow by elimination, combination, re-arrangement and simplification -4 work cells. The research concluded that the waiting time reduced for 63.39%, total process time reduced for 63.04%, from the ideal case process by create efficient flow also can reduce work-in- process (WIP) 61.61% as well as can reduce cost 54.17% .